Effects of shaping-enhanced mirror therapy on motor function in healthy adults: a case-control study - Sergen Öztürk; Özlem Doğan; Alime Nur Kara; Burcu Ersoz Huseyinsinoglu (Bulletin of Faculty of Physical Therapy, 2026)
Abstract While mirror therapy (MT) has shown efficacy in treating various conditions, its practice remains inconsistent due to the lack of a standardized protocol. This study aimed to assess the impact of integrating shaping activities into MT on motor learning, motor dexterity and reaction time of the non-dominant hand in healthy individuals. This case-control study included 30 healthy adults in the MT group (MTG) and 30 age- and gender-matched controls. MTG underwent shaping activities combined with MT twice a week for four weeks, while controls received no intervention and maintained their usual routines. Motor learning, dexterity and reaction time were assessed at baseline and after four weeks using the the Finger Tapping Test (FTT), Roeder Manipulative Aptitude Test [unilateral (RU), bilateral (RB), total (RT)], and the Nelson Hand Reaction Time Test (NHRTT). The mean age of participants was 23.4 ± 2.41 years in both groups. Significant improvements favoring MTG were found in between group comparisons for RU ( p = 0.013), RT ( p = 0.006), and NHRTT ( p